Pengaruh Work Life Balance Dan Beban Kerja Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum Dan Penataan Ruang Pemerintah Provinsi Maluku - Latuconsina, Zainuddin; Sijabat, Asiani; Risambessy, Agusthina; Duwila, Ummi; Sitania, Alvarya C. R. (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to analyze the effect of work-life balance and workload on employee performance. This study used a saturation or census technique in which all members of the population were used as a sample of 50 people. Based on the results of the hypothesis test, it shows that the work-life balance workload does not affect the performance of employees of the Provincial PUPR Office. The results also show that the workload affects the performance of employees of the Provincial PUPR Office.